2016
DOI: 10.1038/srep19416
|View full text |Cite
|
Sign up to set email alerts
|

Down regulated lncRNA MEG3 eliminates mycobacteria in macrophages via autophagy

Abstract: Small non-coding RNA play a major part in host response to bacterial agents. However, the role of long non-coding RNA (lncRNA) in this context remains unknown. LncRNA regulate gene expression by acting e.g. as transcriptional coactivators, RNA decoys or microRNA sponges. They control development, differentiation and cellular processes such as autophagy in disease conditions. Here, we provide an insight into the role of lncRNA in mycobacterial infections. Human macrophages were infected with Mycobacterium bovis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 71 publications
6
99
0
Order By: Relevance
“…Similarly, on the 1 st day of infection majority of the lncRNAs were upregulated on susceptible line relative to two other genetic lines. The expression number of DE’s correlated with the gradient of bacterial load between the three genetic lines: S > C > R. Previous report also indicated correlation of lncRNAs expression with microbial load44. Figure 4 shows abundance of selected hierarchically clustered lncRNAs among genetic lines after infection with Fp .…”
Section: Resultsmentioning
confidence: 72%
“…Similarly, on the 1 st day of infection majority of the lncRNAs were upregulated on susceptible line relative to two other genetic lines. The expression number of DE’s correlated with the gradient of bacterial load between the three genetic lines: S > C > R. Previous report also indicated correlation of lncRNAs expression with microbial load44. Figure 4 shows abundance of selected hierarchically clustered lncRNAs among genetic lines after infection with Fp .…”
Section: Resultsmentioning
confidence: 72%
“…reported that lncRNA-CD244 acted as an epigenetic regulator of IFN-γ and TNF-α production in CD8 + T cells and that it impacts CD8 + T cell immunity against active Mtb infection31. LncRNA-MEG3, which is shown to be a tumour suppressor gene, was downregulated in macrophages with BCG infection, leading to the induction of autophagy and enhanced eradication of intracellular pathogens32. In this study, we revealed that many lncRNAs were differentially expressed in macrophages with H37Ra or H37Rv infection, which indicated that lncRNAs might play an important role in the macrophages response to Mtb infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knockdown of MEG3 resulted in the induction of autophagy, which helped to combat the intracellular BCG infection. Upon treatment with IFN-γ, increased autophagy led to sustained and significant MEG3 downregulation, reinforcing the effective eradication of mycobacteria (14). These investigations have identified a significant relationship between lncRNA and cell autophagy.…”
Section: Introductionmentioning
confidence: 95%